(untitled) (Vietnam Journal of Community Medicine, 2021)
Social anxiety disorder is a common adolescent anxiety disorder with rates ranging from 9.1% to 44% between countries around the world. In Vietnam, research on this disorder is quite limited. Social phobia affects many aspects of life, such as school, work, and increases the risk of depression and suicide in adults. However, finding treatment, the recovery rate is still quite low. So early screening for this disorder is necessary. The study conducted on 430 students participating in the study, the prevalence of phobias on the LSAS scale was 42.3%. 35.7% and 37.4% respectively. Multivariate analysis showed a statistically significant relationship between social phobia and factors such as lack of confidence in appearance, mother’s occupation (p <0.05). Research has given a number of recommendations for early detection and timely intervention solutions towards comprehensive health care for students